2012
DOI: 10.5560/znb.2012-0180
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Imidazolium Salts with the Weakly Coordinating [B(C6F5)4] Anion

Abstract: Graphical Abstract Synthesis and Characterization of Imidazolium Salts with the Weakly Coordinating [B(C6F5)4]– Anion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…According to the vinyl contents shown in Table 2, the presence of ether strongly contributed to the increase of the vinyl content. Dibutyl ether in association with AlCl 3 favors the increase of the exo‐olefin terminal groups, as expected, due to good stabilization of the carbenium ions 32,46 . Moreover, the ether plays an important role in chain transfer for the formation of exo‐olefin groups because the terminal double bonds derived from the chain reaction generate the protonation and the propagation of the monomer 15 .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…According to the vinyl contents shown in Table 2, the presence of ether strongly contributed to the increase of the vinyl content. Dibutyl ether in association with AlCl 3 favors the increase of the exo‐olefin terminal groups, as expected, due to good stabilization of the carbenium ions 32,46 . Moreover, the ether plays an important role in chain transfer for the formation of exo‐olefin groups because the terminal double bonds derived from the chain reaction generate the protonation and the propagation of the monomer 15 .…”
Section: Resultssupporting
confidence: 67%
“…The vinyl contents shown in Table 3 for polymerizations performed with the initial temperature of 30°C displayed a similar behavior to those described in Table 2 for reactions conducted with the initial temperature of 10°C. As the formation of the catalyst complex between ether and AlCl 3 stabilizes the carbenium ions, the vinyl contents increase and polymer yield decreases in the presence of ether, 32,46 as clearly shown in Table 3. The highest vinyl content (around 35 mol%) was obtained in the presence of mixtures of n ‐hexane and toluene, and co‐initiated by ether and water.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently it has been demonstrated that a reduced ion pairing interaction leads to an increased nucleophilicity of perrhenate [59,60] and polyoxomolybdate [61,62] anions, rendering anion-based activation of H 2 O 2 and oxidation of olefins and sulfides possible. Additionally, the synthesis of imidazolium salts containing the [B(C 6 F 5 ) 4 ] − anion showing a weak cation-anion interaction was reported [63]. The tetrafluoroborate anion is also capable of activating hydrogen peroxide by forming hydrogen bonds, which leads to the oxidation of sulfides [65].…”
Section: Introductionmentioning
confidence: 99%